Vasodilator effect of phlomis bracteosa constituents is mediated through dual Endothelium-Dependent and Endothelium-Independent pathways - Khan, A.; Ullah, R.; Mustafa, Mohd Rais; Hussain, J.; Murugan, D.D.; Hadi, A.H.B.A. (2012)
This study describes the vasorelaxant potential of some pure compounds isolated from Phlomis bracteosa L.: marrubiin, phlomeoic acid, and two new constituents labeled as RA and RB. In rat thoracic aortic rings denuded of endothelium, marrubiin, phlomeoic acid, RA, and RB caused relaxation of high K+ (80 mM) and phenylephrine (1 Ã¬M)-induced contractions at the concentration range of 1.0â1000 Ã¬g/mL. Marrubiin, phlomeoic acid, RA, and RB concentration dependently (3.0â10 Ã¬g/mL) shifted the Ca++ curves to the right obtained in Ca++-free medium. The vasodilator effect of marrubiin, phlomeoic acid, RA, and RB was partially blocked by NÃ¹-nitro-L-arginine methyl ester in endotheliumintact aorta preparations. These results reveal that P. bracteosa constituents: marrubiin, phlomeoic acid, RA, and RB exhibit vasodilator action occurred via a combination of endothelium-independent Ca++ antagonism and endotheliumdependent NÃ¹-nitro-L-arginine methyl ester-sensitive nitric oxide-modulating mechanism.